Prison a/r/tography: the aesthetic of 'captive' masculinities - Chinhanu, Chiedza Adelaide (Department of Drama, 2017)
Contemporary artists have been successful in breaking into prisons and persuading the prison institutions, the general public and prison educators to legitimize artistic activity. However, the discourses on prison theatre have been largely dominated by therapeutic and rehabilitative agendas, possibly at the expense of theatre practice - its aesthetic strategies, and aural and visual qualities. This research comes against such a background. The research project was developed in response to the debates and concerns about artistic work in applied prison theatre. It was located at the borders of what can be articulated about aesthetic intervention 'without purpose' in a prison setting; - without purpose in the sense of eschewing big claims of social and psychological efficacy. Through the practice of a/r/tography, which is a means of inquiry through a method of art making, the research examined what is possible about the work. Of particular interest was the potential to explore possibilities for aesthetic intervention understandings and nuances in prison theatre. Be that as it may, although there was a conscious moving away from the applied umbrella as overtly instrumentalist, it can be argued from the findings that there is a possible tension of falling under the umbrella.